Digital media and linguistic evaluation between the need to stay and the idea of dispensing - Abbas, Mohammed Abdullah (ALBAHITH ALALAMI, 2022)
In spite of the contemporary development over the world in pertaining of modernization and its differences about the transformation of the knowledge but, the important instrument to transfer the thoughts and information did not have change except the language. So the evolutionary process became as a torrent or fusillade above the cliff which drifted anything. So that the objective inquiry and impressed with varieties of development the casement to evaluate the linguistic or re - correction highlight article in order to preserve on the origins of the language and its sobriety.Today, we have different correspondence and social media as Email, Website, an another of connection on the Internet, which resembled among the various societies. Furthermore, it had been given up the form of assessment within its linguistic origins that need accuracy and precise in right Arabic words.Finally, the process of research in exploring the gravity of language to address the specialization and the responsibility of spread an important language and means of maintaining all knowledge fields in language.